Systematic color tuning of a family of firefly oxyluciferin analogues suitable for OLED applications. (March 2016) - Min, Chun-Gang; Leng, Yan; Yang, Xi-Kun; Huang, Shao-Jun; Ren, Ai-Min
Abstract: The firefly oxyluciferin analogues have great potential application in organic light-emitting devices because of their high fluorescent efficiency. The emission color of these analogues can be tuned by chemical functionalization. To reveal the molecular structures, optoelectronic properties, and structure–property relationships of these analogues, an in-depth theoretical investigation was elaborated via quantum chemical calculation. The calculated ionization potentials, electron affinities, and reorganization energies show that introduction of dimethylamino and double bond can significantly affect the carrier injection and transport characteristics. We also calculated the singlet-to-triplet exciton-formation cross-section ratio ( σ S / σ T ), the exciton formation fractions ( χ s ), the absorption and emission spectra. The calculated σ S / σ T values range from 1.00 to 10.17, and the corresponding χ s are ca. 0.25–0.77. The calculated emission spectra range from 403.93 to 631.09 nm. It can be deduced that these studied firefly oxyluciferin analogues can serve as efficient blue, green, orange and red light-emitting electroluminescent materials. Highlights: The emission color of these analogues can be tuned by chemical functionalization. Double bond can affect the carrier injection and transport characteristics. These analogues can serve as blue, green, orange and red light-emitting materials. The radiative lifetimes of some analogues are close to nature firefly oxyluciferin. Some derivates were used as highly efficient fluorescent OLED materials.